Robust stability and physiological correlates of infants’ patterns of regulatory behavior in the still-face paradigm at 3 and 9 months - Barbosa, Miguel (2019)
This study examined the stability of three patterns of infant regulatory behavior identified in the face-to-face still-face (FFSF) paradigm at 3 and 9 months—social-positive oriented, distressed-inconsolable, and self-comfort oriented—and whether variations in infants’ heart-rate were correlated with them. Although some studies have examined the stability of discrete infant behaviors, none have investigated the stability of early regulatory patterns across FFSF episodes over time. Healthy full-term infants and their mothers (N = 112) were videotaped in the FFSF when infants were 3 and 9 months old. Infants’ regulatory patterns were scored with the Coding System for Regulatory Patterns in the FFSF. Infants’ heart-rate level during each episode of the FFSF was also assessed. The social-positive-oriented pattern was the most prevalent at both ages. Cross-tabulation analysis showed a robust stability (Cohen’s κ = .72) of the regulatory patterns from 3 to 9 months. The heart-rate level of infants with a social-positive-oriented pattern at 3 and 9 months showed recovery to baseline levels following the still-face. In contrast, the heart-rate level of infants with a distressed-inconsolable pattern at 9 months increased from the still-face to the reunion episode, whereas the heart-rate level of infants with a self-comfort-oriented pattern at 9 months did not change from the still-face to the reunion episodes. These results suggest that infants exhibit distinct organized regulatory patterns as early as 3 months that are stable over a 6-month interval and associated with variations in infants’ physiological responses across FFSF episodes at both ages.